WHAT MAKES A GOOD PROGRAMMER? - Cegielski, Casey G.; Hall, Dianne J. (Communications of the ACM, 2006)
The article focuses on the characteristics of successful and effective computer programmers. The article presents the results of research into whether an individual's theoretical value beliefs, such as desire for structure and testing; coupled with characteristics such as cognitive ability and personality; affects how effective an individual is at computer programming. The study was conducted between 2003 and 2004 at a university in the Southeastern United States. The research concluded that an individual's theoretical value beliefs and personality affected programming effectiveness more than cognitive ability.